Figurative Language Analysis on The Taming of the Shrew Drama Script by William Shakespeare - Hendy Reynaldi Pratama; Rakhmat Wahyudin Sagala (British : Jurnal Bahasa dan Sastra Inggris, 2022)
This study deals with types of figurative languages and its meaning on drama entitled The Taming of the Shrew by William Shakespeare. The objectives of the study were to find out the types of figurative language then describe the meanings and find the dominantly of figurative languages found in drama entitled The Taming of The Shrew by William Shakespeare. The researcher used descriptive qualitative method to collect the data. The data was analysed through Taylor (1981) that the three phases include data reduction, data display and conclusion drawing and verification. The source of the data was taken from the book by William Shakespeare entitled The Complete Works of William Shakespeare. The finding of the research which showed some types of figurative language used in drama entitled The Taming of the Shrew by William Shakespeare and there were five types of figurative language found in the drama. The details were four statements of personification, three statements of simile, five statements of metaphor, three statements of hyperbole, and two statements of irony. And figurative language dominantly appeared is metaphor with five total number of statements. Keywords: Figurative Language, The Taming of the Shrew, William Shakespeare, Drama Script, Literary Work.